TREATMENT PROCEDURES FOR ANEMIA IN EXPERIMENTAL ANIMALS WITH LOCAL VEGETABLE PROTEIN PRODUCTS - Mavlonjon Nasirdinov; Nizom J. Ermatov (Central Asian Journal of Medicine, 2022)
To model the anemia, 4 groups used 5 female rats without white offspring, the first group received an equivalent amount of distilled water for the control group, the second group was given a mash for experimental animals, the third was given a pea and the fourth was given a bean. On 10, 20 and 30 days of the experiment, blood was taken from 0,5 ml for analysis of the level of hemoglobin, hematocrit level and erythrocytes in animals. The experiment showed that hemoglobin in the blood after blood loss in animals was 72,16% of the results of 2 days of anemia compared to the background level of the control group, 65,28% in the mosh-given group, 68,66% in those who received beans, and 70,92% in those who consumed peas. On the 10th day of the experiment for the "control" group, the hemoglobin content was 10% lower than in the experimental group, and by 115959 g/L, by the 20th day of the experiment, this indicator mark even decreased-98,82 g/L, that is, the differences in the experimental group were on average 12% for mosh and peas, 10% for beans. On the 20 - th day of the experiment and 30-th day of the experiment, the amount of erythrocytes in the animals in the experimental group was compared with the initial signs.